Feasibility Analysis of Wororez Msme Businesses Seluang Cripsy and Bilis Cripsy - Yusuf, Bahruddin; Riani, Maria Ulfah (Agrikan Jurnal Agribisnis Perikanan, 2025)
Wororez UMKM is one of the UMKM that produces Seluang Cripsy fish and Bilis Cripsy which are currently still very rarely produced around South Kalimantan. This UMKM is located in the Sukarelawan Asri complex, Block B Number 19, Sukarelawan Street, North Loktabat Village. The objectives of this study are: to determine the feasibility of the business from the profits of Wororez UMKM, to determine the R/C ratio of Wororez UMKM, to determine the BEP of each Wororez UMKM product. This study was conducted from February to April 2025. The data analysis methods used are cost analysis, revenue, profit, R/C ratio and Break Even Point. The results of this study indicate that the Seluang Cripsy fish and Bilis Cripsy fish business can provide great profits. The sale of Seluang Cripsy fish and Bilis Cripsy can provide promising business opportunities because the profits obtained per year reach Rp. 240,675,333.33. From the calculation of the feasibility of the business analysis, R/C = 2.26 is obtained. For BEP production and prices produced by UMKM Wororez, both Seluang Crispy fish 100 g and 50 g and Bilis Crispy fish 100 g and 50 g are all above the break-even point. Because R/C is greater than 1 and BEP production and prices for all the products above are above the break-even point, the crispy fish business is feasible to do.